Nutrition and behaviour change communication strategies for Solomon Islands and Vanuatu - Ekesa, Beatrice; Nabuuma, Deborah (2024)
Nutrition and Behaviour Change Communication strategies were participatorily developed to guide nutrition interventions and communication that enhances community awareness and capacity to increase access to and consumption of healthy diets in Tanna, Vanuatu and Malaita, Solomon Islands. The strategies focused on access to, utilisation and consumption of healthy sustainable diets from diverse locally available foods, while also incorporating and/or addressing the knowledge, attitudes, beliefs, skills, self-efficacy, and norms that support access to and consumption of healthy sustainable diets. This brief presents the context, development process and highlights from the two strategies.